Comparison of Ayer’s Spatula Versus Cytobrush in Adequacy of Sample Obtained for Pap Smear - Gulwish Salahuddin, Tahira Jabeen, Ayesha Naz, Rukhsana Shaheen Afzal, Khairun Nisa, Iram Mushtaq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the adequacy of Pap-smear in the same patient obtained by Ayer’s spatula and cytobrush. Study design: Comparative cross-sectional study Methodology: One hundred and fifty patients were enrolled. Each patient was subjected to both the tools i.e. cytobrush and Ayer’s spatula. Results: The mean age was 41.6±10.4 years. 83.3% of patients using Ayer’s spatula while 94.7% was using cytobrush and statistically the significant (P=0.002) results were found. Conclusion: Sampling with cytobrush resulted in better percentage of adequate samples as compared to Ayer’s spatula.